Molecularly imprinted sensors : overview and applications - Li, Songjun (Elsevier, 2012)
Molecular imprinting is a rapidly growing field with wide-ranging applications, especially in the area of sensor development, where the process leads to improved sensitivity, reliability, stability, and reproducibility in sensing materials. Molecularly Imprinted Sensors in Analytical Chemistry addresses the most recent advances and challenges relating to molecularly imprinted polymer sensors, and is the only book to compile this information in a single source. From fundamentals to applications, this material will be valuable to researchers working in sensing technologies for pharmaceutical separation and chemical analysis, environmental monitoring and protection, defense and security, and healthcare. Provides a systematic introduction to the different types of MIP-based sensors and reviews the basic principles behind each type of sensor Includes state-of-the-art methodology supported by comparisons and discussions from leading experts in the field Covers all types of sensing modes (optical, electrochemical, thermal, acoustic, etc.), materials and platforms Appeals to a multidisciplinary audience of scientists and graduate students in a wide variety of fields, including chemistry, biology, biomedical science and engineering, and materials science and engineering.